Supervised classification of pathologies in asphalt pavements surface from a Remote Piloted Aircraft (RPA) - Legramanti, Gabriela; Duarte, Renato D; Gomes Junior, Ernesto Valdecir; Dallagnol, Sergio Luiz; Rinaldi Bisconsini, Danilo; Dos Santos Felipetto, Henrique; De Moraes, Liza (Revista ALCONPAT, 2023)
Pathology identification is a routine activity in Pavement Management Systems (PMS) for decision-making about Maintenance and Rehabilitation (M&R) services. Traditional methods can be time-consuming, disrupt traffic, and cause accidents. This study evaluated pathologies on asphaltpavements using walking survey, manual classification of images from a Remotely Piloted Aircraft (RPA), and supervised classification. Manual classification resulted in 93.1% accuracy compared to 32.7% in supervised classification. The study concludes that the RPA can evaluate pathologies in asphalt pavements, providing time savings and safety. Keywords: pavement; pavement management; pathologies; Remotely Piloted Aircraft; RPA.